2019
DOI: 10.1155/2019/8987436
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Rhodococcus equi: An Insight into Genomic Diversity and Genome Evolution

Abstract: Rhodococcus equi, a member of the Rhodococcus genus, is a gram-positive pathogenic bacterium. Rhodococcus possesses an open pan-genome that constitutes the basis of its high genomic diversity and allows for adaptation to specific niche conditions and the changing host environments. Our analysis further showed that the core genome of R. equi contributes to the pathogenicity and niche adaptation of R. equi. Comparative genomic analysis revealed that the genomes of R. equi shared identical collinearity relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The genus Rhodococcus , a group of facultative aerobic Gram-positive bacteria, belongs to nocardiaceae, Corynebacterium suborder, and is widely distributed in rocks, groundwater, soil, marine sediments, insects, animals and plants ( Gao and Gupta, 2012 ; Vazquez-Boland et al., 2020 ). Among the 57 species in the genus Rhodococcus , at least six species ( R. equi , R. erythropolis , R. ruber , R. gordoniae R. fascians and R.defluvii ) have been proved to be related to animal and plant pathogenicity ( Sangal et al., 2015 ; Anastasi et al., 2016 ; Canetti et al., 2019 ; Ying et al., 2019 ). Among these six species, R. equi is the main pathogen of human infection.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Rhodococcus , a group of facultative aerobic Gram-positive bacteria, belongs to nocardiaceae, Corynebacterium suborder, and is widely distributed in rocks, groundwater, soil, marine sediments, insects, animals and plants ( Gao and Gupta, 2012 ; Vazquez-Boland et al., 2020 ). Among the 57 species in the genus Rhodococcus , at least six species ( R. equi , R. erythropolis , R. ruber , R. gordoniae R. fascians and R.defluvii ) have been proved to be related to animal and plant pathogenicity ( Sangal et al., 2015 ; Anastasi et al., 2016 ; Canetti et al., 2019 ; Ying et al., 2019 ). Among these six species, R. equi is the main pathogen of human infection.…”
Section: Introductionmentioning
confidence: 99%
“…The phylogenetic analyses have shown that “ R. equi ” has a high degree of core genome (conserved gene set) similarity with non-pathogenic environmental rhodococcal species [ 96 ]. There are genes involved in protein biosynthesis, metabolism, transport, and signal transduction, which can be associated with both adaptation and virulence.…”
Section: Ubiquity Of Rhodococcus and Existence Of Pathogenic Speciesmentioning
confidence: 99%
“…In contrast, the transcription (K, 936 genes), carbohydrate transport and metabolism (G, 655 genes), and inorganic ion transport and metabolism (P, 645 genes) categories occurred more frequently in the accessory genome. These COG categories are fundamental for niche adaptation because they represent functions that induce the activation of related internal systems and introduce various external sources [ 57 ]. The unique genome showed high ratios of genes in the mobilome (X, 69 genes) and defence mechanism (V, 58 genes) categories (Table S6), which can be mediated by rapid sequence evolution or HGT [ 58 ].…”
Section: Resultsmentioning
confidence: 99%